Environmental risks and sphingolipid signatures in adult asthma and its phenotypic clusters: a multicentre study. Issue 3 (16th June 2022) - Wu, Chao-Chien; Wang, Chin-Chou; Chung, Wen-Yu; Sheu, Chau-Chyun; Yang, Yi-Hsin; Cheng, Ming-Yen; Lai, Ruay-Sheng; Leung, Sum-Yee; Lin, Chi-Cheng; Wei, Yu-Feng; Lin, Ching-Hsiung; Lin, Sheng-Hao; et al.
Abstract : Background: Adult asthma is phenotypically heterogeneous with unclear aetiology. We aimed to evaluate the potential contribution of environmental exposure and its ensuing response to asthma and its heterogeneity. Methods: Environmental risk was evaluated by assessing the records of National Health Insurance Research Database (NHIRD) and residence-based air pollution (particulate matter with diameter less than 2.5 micrometers (PM2.5 ) and PM2.5 -bound polycyclic aromatic hydrocarbons (PAHs)), integrating biomonitoring analysis of environmental pollutants, inflammatory markers and sphingolipid metabolites in case–control populations with mass spectrometry and ELISA. Phenotypic clustering was evaluated by t-distributed stochastic neighbor embedding (t-SNE) integrating 18 clinical and demographic variables. Findings: In the NHIRD dataset, modest increase in the relative risk with time-lag effect for emergency (N=209 837) and outpatient visits (N=638 538) was observed with increasing levels of PM2.5 and PAHs. Biomonitoring analysis revealed a panel of metals and organic pollutants, particularly metal Ni and PAH, posing a significant risk for current asthma (ORs=1.28–3.48) and its severity, correlating with the level of oxidative stress markers, notably Nε-(hexanoyl)-lysine (r=0.108–0.311, p<0.05), but not with the accumulated levels of PM2.5 exposure. Further, levels of circulating sphingosine-1-phosphate and ceramide-1-phosphate were found to discriminate asthma (p<0.001 and p<0.05, respectively), correlating with the levels of PAH (r=0.196, p<0.01) and metal exposure (r=0.202–0.323, p<0.05), respectively, and both correlating with circulating inflammatory markers (r=0.186–0.427, p<0.01). Analysis of six phenotypic clusters and those cases with comorbid type 2 diabetes mellitus (T2DM) revealed cluster-selective environmental risks and biosignatures. Interpretation: These results suggest the potential contribution of environmental factors from multiple sources, their ensuing oxidative stress and sphingolipid remodeling to adult asthma and its phenotypic heterogeneity.